The Impact of the Abraham Accords on Geopolitical Dynamics of the Middle East - Rohulia, Karyna (Mediaforum : Analytics, Forecasts, Information Management, 2023)
The Abraham Accords, signed in 2020, have emerged as a watershed moment in the geopolitical landscape of the Middle East, marking a significant shift in regional dynamics. This scientific article provides an in-depth analysis of the Accords’ impact on the Middle East, exploring the multifaceted consequences of this historic realignment. Focusing on the normalization of relations between Israel and several Arab nations, including the United Arab Emirates, Bahrain, Sudan, and Morocco, the study examines the broader geopolitical implications, with particular attention to the redefinition of regional alliances, economic and technological cooperation, and the nuanced effects on the Israeli-Palestinian conflict.The article delves into the strategic motivations behind the Accords and their influence on the traditional Arab-Israeli relations, underscoring a paradigm shift from longstanding animosity to a newfound cooperation based on shared interests, particularly in security and economic spheres. It evaluates the economic opportunities catalyzed by the Accords, such as increased trade and joint technological ventures, which promise to foster a new era of prosperity and interdependence in the region.Furthermore, the analysis addresses the complex implications for the Israeli-Palestinian peace process, assessing the potential for the Accords to reshape the future trajectory of this long-standing conflict. While acknowledging the initial concerns of sidelining the Palestinian issue, the article explores the possibility of these agreements creating new platforms for dialogue and conflict resolution.The article also contextualizes the Accords within the broader regional and international geopolitical framework, analyzing how this development reflects the changing priorities and strategies of Middle Eastern states in response to regional threats, global economic trends, and the evolving role of external powers. The challenges and prospects for the future of the Abraham Accords are critically examined, considering the sustainability of these agreements amidst the dynamic and often volatile regional environment.In conclusion, this comprehensive study posits that the Abraham Accords signify a momentous shift in Middle Eastern geopolitics, with potential ramifications that extend beyond the immediate signatories. The Accords herald a new chapter in the region's history, where diplomatic engagement and economic collaboration may pave the way for a more stable and integrated Middle East, albeit with remaining challenges and uncertainties.